α-Tocopherol Attenuates Oxidative Phosphorylation of CD34(+) Cells, Enhances Their G0 Phase Fraction and Promotes Hematopoietic Stem and Primitive Progenitor Cell Maintenance - Rodriguez, Laura (Biomolecules, 2021)
Alpha tocopherol acetate (αTOA) is an analogue of alpha tocopherol (αTOC) that exists in the form of an injectable drug. In the context of the metabolic hypothesis of stem cells, we studied the impact of αTOA on the metabolic energetic profile and functional properties of hematopoietic stem and progenitor cells. In ex vivo experiments performed on cord blood CD34(+) cells, we found that αTOA effectively attenuates oxidative phosphorylation without affecting the glycolysis rate. This effect concerns complex I and complex II of the mitochondrial respiratory chain and is related to the relatively late increase (3 days) in ROS (Reactive Oxygen Species). The most interesting effect was the inhibition of Hypoxia-Inducible Factor (HIF)-2α (Hexpression, which is a determinant of the most pronounced biological effect—the accumulation of CD34(+) cells in the G0 phase of the cell cycle. In parallel, better maintenance of the primitive stem cell activity was revealed by the expansion seen in secondary cultures (higher production of colony forming cells (CFC) and Severe Combined Immunodeficiency-mice (scid)-repopulating cells (SRC)). While the presence of αTOA enhanced the maintenance of Hematopoietic Stem Cells (HSC) and contained their proliferation ex vivo, whether it could play the same role in vivo remained unknown. Creating αTOC deficiency via a vitamin E-free diet in mice, we found an accelerated proliferation of CFC and an expanded compartment of LSK (lineage(negative) Sca-1(+)cKit(+)) and SLAM (cells expressing Signaling Lymphocytic Activation Molecule family receptors) bone marrow cell populations whose in vivo repopulating capacity was decreased. These in vivo data are in favor of our hypothesis that αTOC may have a physiological role in the maintenance of stem cells. Taking into account that αTOC also exhibits an effect on proliferative capacity, it may also be relevant for the ex vivo manipulation of hematopoietic stem cells. For this purpose, low non-toxic doses of αTOA should be used.